Studi Ma’ānī dan Asbāb Wurūd Hadis Tentang Manusia yang Paling Utama - Badani, Rachmat (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research aims to determine the content of the hadith of Ka'ab bin Mālik regarding the most important human explanations. This research is descriptive research using library method and approaches of Study of Ma'ānī Hadith and Sabab Wurūd Hadith. The results of this research found several things. First, the hadith of Ka'ab bin Mālik is a very weak hadith because it was narrated through Mu'āwiyah bin Yaḥya which was weakened by the ulama of al-Jarḥ wa al-Ta'dīl. However, this hadith has also been narrated from other channels, namely from the Abū Ẓār hadith which is also a little weak and the hadith of 'Umar bin al-Khattāb with hasan sanad, so that some hadith scholars have judged this hadith as authentic or at least as hasan hadith. Second, the Sabab Wurūd hadith of Ka'ab bin Mālik was a sahabah's question to the Messenger of Allah about who is the most important human being in the sight of Allah. The answer given by Rasulullah saw. adjust to the situation of the sahabah who asks him. Third, this hadith contains the message that the most important human beings are believers, children of believers, and fathers of believers. This is based on the content of the Bukhārī hadith where the Prophet said that the truly a noble person, the son of a noble person, the son of a noble person, the son of a noble person, is Yūsuf bin Ya'qūb bin Ishāq bin Ibrāhīm, the beloved of Allah.